Egyptian revolution 2.0 political blogging, civic engagement, and citizen journalism - El-Nawawy, Mohammed 1968-; Khamis, Sahar (The Palgrave Macmillan series in international political communication, 2013)
This book sheds light on the growing phenomenon of cyberactivism in the Arab world, with a special focus on the Egyptian political blogosphere and its role in paving the way to democratization and socio-political change in Egypt, which culminated in Egypt's historical popular revolution